Development of a Socio-Scientific Issues-Based Electronic Learner Activity Sheets to Enhance Learners’ Critical Thinking Skills on the Topic of Hydrocarbons - Wanda Hanna Sajida; Rusly Hidayah; Angela Shrestha (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
The transformation of the 21st century necessitates that educational institutions produce learners with essential competencies, particularly critical thinking skills (CTS). Learners’ CTS in hydrocarbon topics remain at a relatively low level. Development of these skills is achievable through the presentation of controversial socio-scientific issues in society as stimuli for training structured critical thinking processes. This research aims to determine the feasibility of socio-scientific issues (SSI)-based electronic learner activity sheets (E-LAPD) in enhancing learners' CTS. The study employed the 4D model, executed up to the develop stage. A field trial of the E-LAPD was conducted with 36 learners from class XI-2 at SMAN 20 Surabaya. The research instruments included pretest and post-test sheets for CTS and cognitive domains, as well as review, validation, observation, and learner response questionnaires. The developed E-LAPD was declared feasible based on a median score of 5 categorized as 'highly valid.' Learners’ responses reached 91.67%, further supported by s learners’ activity observations reached 95.56%. The E-LAPD proved effective, as evidenced by a p-value (sig.) of 0.000 in the t-test, indicating that post-test scores significantly outperformed pretest scores. Additionally, the effectiveness of E-LAPD was confirmed by an N-gain score of 0.686, categorized as 'moderate'. further indicate that the SSI-based E-LAPD was effective in supporting the improvement of students’ CTS in hydrocarbon learning